2021
DOI: 10.1080/21678421.2021.1936556
|View full text |Cite
|
Sign up to set email alerts
|

Case-control study in ALS using the National ALS Registry: lead and agricultural chemicals are potential risk factors

Abstract: Objective: To identify occupational risk factors for ALS using well-characterized participants with ALS (P-ALS), sibling controls (S-controls), and matched population controls (P-controls) within the National ALS Registry. We also compared oxidative stress (OS) biomarkers between groups. Methods: P-ALS were recruited over 4 years. Demographic, socioeconomic, and medical data were ascertained from medical records and structured interviews. P-ALS were followed prospectively for 2 years or until death, whichever … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…Ultimately, the goal is for more in-depth research to further describe the role these risk factors play in the onset and progression of ALS. • Heavy metals: bioavailable methylmercury 22 • Heavy Metals: lead, 19,20,22 inorganic mercury 22,24 • Agricultural chemicals: MCPB (4-[2-methyl-4-chlorophenoxy]-butyric acid), Terbacil, glyphosate, paraquat, carbaryl, chlorpyrifos, Mancozeb (manganese-zinc ethylene-bis-di-thiocarbamate) 13 • Agricultural chemicals: 2,4-D (2,4dicholorophenoxyacetic acid), permethrin 13 • Water bodies: full-time residence within 2 miles of a water body, frequent water-related activities (water skiing, boating, sailing, kayaking) 20 • Trauma/injury: head trauma, severe electrical burn/electrocution 25 Metabolites or metabolic pathways…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultimately, the goal is for more in-depth research to further describe the role these risk factors play in the onset and progression of ALS. • Heavy metals: bioavailable methylmercury 22 • Heavy Metals: lead, 19,20,22 inorganic mercury 22,24 • Agricultural chemicals: MCPB (4-[2-methyl-4-chlorophenoxy]-butyric acid), Terbacil, glyphosate, paraquat, carbaryl, chlorpyrifos, Mancozeb (manganese-zinc ethylene-bis-di-thiocarbamate) 13 • Agricultural chemicals: 2,4-D (2,4dicholorophenoxyacetic acid), permethrin 13 • Water bodies: full-time residence within 2 miles of a water body, frequent water-related activities (water skiing, boating, sailing, kayaking) 20 • Trauma/injury: head trauma, severe electrical burn/electrocution 25 Metabolites or metabolic pathways…”
Section: Discussionmentioning
confidence: 99%
“…First, many of the publications identified by researchers have not been published long enough to be cited. Six additional publications identified during our search process have been published Subgroup analysis: insufficient sample sizes for specific subpopulations 20,22,23,30 • Larger cohort studies 22,23 • Targeted population sampling (e.g., exposure to water bodies, specific drug/therapeutic profiles, specific familial/genetic patterns, small-area populations, geographical "hot spots") 20,22,23,30 Latency analysis: insufficient detail on exposure timing and duration in reported information 13,20,22 • Additional information (e.g., prediagnostic exposures, residential history, weather-related exposure patterns, distance to chemical use) 13 • Biological specimen (estimates for exposure dose, bioaccumulation) 13,20 • Prospective cohort studies 13,22 Confounding: challenges related to identifying ideal population-based control cohorts 19 • Standardized methodologies for control recruitment (e.g., sibling controls, matched population controls) 9,19 • Prospective cohort studies 19 Causal inference: unclear cause-effect relationship between observed exposures and disease outcomes 20,22,24,30 • Prospective cohort studies 22 • Experimental studies for identified risk factors 22 • Mechanistic studies for less-studied chemicals 13 Clinic-based ALS cohorts (e.g., hospital, multicenter)…”
Section: Limitationsmentioning
confidence: 99%
“…All samples and data came from participants that provided written, informed consent for genetic studies that had been IRB-approved at each contributing center. The study cohort includes participants from the Genomic Translation for ALS Care (GTAC study), the Columbia University Precision Medicine Initiative for ALS, the ALS COSMOS Study Group, the PLS COSMOS Study Group, the New York Genome Consortium, and the ALS Sequencing Consortium (IRB- For PLS, explicit criteria requiring >3 years of symptoms without conversion to ALS were used for 79 of the 172 PLS participants (14). The criteria used for the remaining PLS diagnoses were not available.…”
Section: Study Populationmentioning
confidence: 99%
“…Another study also supported lead exposure (odds ratio ∼2) and a ratio of 7 among occupations that included exposure to both lead and agricultural pesticides. 32…”
Section: Environmental Risk Factors and Exposuresmentioning
confidence: 99%
“…Another study also supported lead exposure (odds ratio ;2) and a ratio of 7 among occupations that included exposure to both lead and agricultural pesticides. 32 Sorting out the direct roles of trauma and environmental exposures in the cause of ALS is important but elusive, for there are many patients who develop the disease but have experienced none of the known risk factors.…”
Section: Environmental Risk Factors and Exposuresmentioning
confidence: 99%